PENGARUH DUKUNGAN SOSIAL TEMAN SEBAYA UNTUK MENGURANGI TINGKAT STRES PADA MAHASISWA PSIKOLOGI YANG SEDANG MENYUSUN SKRIPSI DI UNIRA MALANG - RR. Hesti Setyodyah Lestari; Riris Wijayanti (LPSDI Bina Patria, 2023)
Everyone goes through periods of stress. Stress is considered a mental illness in psychology. This has been widely accepted among students, especially those in their final semester of school, in the context of learning stress. Providing social support to your neighbors and friends is another approach to reducing stress. Utilizing a quantitative methodology, this investigation. The goal of this study was to discover how peer social support influences stress reduction in students enrolled at Unira Malang. The sample and study area are 45 students who are currently completing their dissertations in 2017-2018. The analysis was carried out using verifiable descriptive analysis.According to the descriptive analysis of peer social support variables, 2.2% of students received low support, 11.1% received sufficient support, 51.0% received high support, and 35.5% received very high support. In addition, 11.1% of students got quite good help from friends, 82.2% of students got good help, and as much as 6.7% got very good help from friends.The significance value (sig) for the hypothesis test is 0.00 less likely to be 0.05, eliminating H0 and retaining Ha, indicating that